KEWENANGAN POSITIVE LEGISLATURE MAHKAMAH KONSTITUSI DALAM PENGUJIAN UNDANG-UNDANG TERHADAP UNDANG-UNDANG DASAR 1945: The Authority of the Legislative Body of the Constitutional Court in Judicial Review of the Constitution 1945 - M. Noor Harisudin; Fika Alfiella (UIN Kiai Haji Achmad Siddiq Jember, 2022)
This study aims to analyze the authority of the Constitutional Court in setting new norms in cases of judicial review of the Constitution. Basically the Constitutional Court is a branch of judicial power, but the fact is that the Constitutional Court has several times made decisions containing new norms in judicial review of the Constitution. This research uses normative juridical research and library research (library) which focuses on library activities to obtain data without conducting research in the field. The results of this study are: 1) The authority of the Constitutional Court has been regulated explicitly in Article 24 C of the 1945 Constitution, as such, the decision of the Constitutional Court which is constitutionally positive in Indonesia is not contradictory/constitutional. 2) The decision of the Constitutional Court is final and binding since it is officially pronounced or read out in an open plenary session which is open to the public. The final decision of the Constitutional Court in addition to having binding power, also has evidentiary power and executorial power, the Constitutional Court's decision is the final word for the enforcement of a legal norm/stipulation whose position is equal to the law itself. 3) Since its establishment until now, the Constitutional Court has received requests for Judicial Review (PUU) as many as 1041 (one thousand and forty-one) cases. Among them there are several decisions that establish new norms which are then followed up by the government, one of which is Constitutional Court Decision Number 128 /PUU-XIII/2015. Then PERMENDAGRI Number 67 of 2017 was born Studi ini bertujuan untuk menganalisis kewenangan Mahkamah Konstitusi dalam menetapkan norma baru pada perkara pengujian undang-undang terhadap Undang-Undang Dasar. Pada dasarnya Mahkamah Konstitusi merupakan cabang kekuasaan yudikatif namun faktanya Mahkamah Konstitusi sudah beberapa kali menetapkan putusan yang berisi norma baru dalam pengujian undang-undang terhadap Undang- Undang Dasar. Penelitian ini menggunakan jenis penelitian yuridis normatif dan library research (kepustakaan) yang memusatkan kegiatan pada perpustakaan untuk memperoleh data tanpa melakukan riset di lapangan. Hasil dari penelitian ini adalah : 1) Kewenangam Mahkamah Konstitusi telah diatur secara eksplisit dalam Pasal 24 C Undang-Undang Dasar 1945, sebagaimana hal terssebut maka putusan Mahkamah Konstitusi yang bersifat positive legislature secara konstitusional di Indonesia tidak bertentangan/Konstitusional. 2) Putusan Mahkamah Konstitusi bersifat final dan mengikat (final and binding) sejak resmi diucapkan atau dibacakan dalam sidang pleno terbuka yang terbuka untuk umum. Putusan final Mahkamah Konstitusi selain memiliki kekuatan mengikat, juga memiliki kekuatan pembuktian dan kekuatan eksekutorial, maka putusan Mahkamah Konstitusi menjadi kata akhir dari pemberlakuan sebuah norma/ketentuan undang-undang yang kedudukannya setara dengan Undang-Undang itu sendiri. 3) Sejak berdiri hingga sekarang, Mahkamah Konstitusi telah menerima permohonan Pengujian Undang-Undang (PUU) sebanyak 1041 (seribu empat puluh satu) perkara Diantaranya terdapat beberapa putus an yang menetapkan norma baru yang kemudian ditindak lanjuti oleh pemerintah salah satunya, Putusan Mahkamah Konstitusi Nomor 128/PUU-XIII/2015. maka lahir PERMENDAGRI Nomor 67 tahun 2017.